Strategi Habituasi Pembelajaran Sebagai Hidden Curriculum Untuk Meningkatkan Karakter Islami Siswa di SMA Muhammadiyah 25 Setiabudi Pamulang - Dwita, Rahmi; Suryadi, Ahmad (Jurnal Pendidikan Islam, 2025)
This study aims to describe and analyze the strategy of learning habituation as part of the hidden curriculum in shaping and enhancing Islamic character among students at SMA Muhammadiyah 25 Setiabudi Pamulang. Islamic character is a crucial aspect of education that is instilled not only through Islamic Religious Education subjects but also through habitual practices in daily school life. This research uses a qualitative approach with a case study method. Data were obtained through interviews, observations, and documentation involving teachers, students, and educational staff. The results show that the habituation strategy is implemented through routine activities such as congregational prayers, Qur'an recitation, collective prayers, and the cultivation of polite behavior. These habituations are consistently applied and integrated into the school culture, thus fostering Islamic values such as discipline, responsibility, honesty, and mutual respect. The role of teachers, parents, and the guidance and counseling approach also supports the success of this strategy. Despite challenges, such as the lack of continuity of habituation at home, the synergy between school and family becomes a key factor in sustainably instilling Islamic character. Therefore, the habituation strategy as a hidden curriculum has proven effective in improving students’ Islamic character and can serve as a model for strengthening character education based on Islamic values in schools.